Local wisdom-infused experiential learning and its effects on reading literacy: a meta-analysis - Huda, Tiyas Abror; Setiyadi, Ag. Bambang; Haenilah, Een Yayah; Rusminto, Nurlaksana Eko; Sinaga, Risma Margaretha; Hamid, Mustofa Abi (Journal of Education and Learning (EduLearn), 2025)
Numerous meta-analysis studies have been undertaken on the topic of culturally embedded learning. Insufficient study has been undertaken on culturally integrated learning as a means to enhance reading abilities. The objective of this study is to assess and evaluate the impact of learning enriched by local culture on reading proficiency. This research was conducted using meta-analysis. The document search conducted using Google Scholar yielded 14 document papers published between 2019 and 2023. The research design included a contrast group with random effects model, incorporating a corrected effect size. The investigation employed Jeffreys’s Amazing Statistics Program (JASP) software to compute means aggregate errors, generate forest plots, and assess publication bias. The research reported a statistically significant difference (SE=2.091) between the groups that used local knowledge and standard methods in the learning process. The findings also indicated that incorporating local culture has a significant and favorable impact (with a p value of less than 0.05, namely 0.001) on reading proficiency. This demonstrates that incorporating local culture into the learning process is successful in enhancing students' reading proficiency. Therefore, this study recommends that teachers incorporate local culture as a subject in their teaching to enhance students' reading proficiency.